The role of biology teacher’s Pedagogical Content Knowledge (PCK) on the quality of learning: A review - S Wulandari; N Y Rustaman; A Widodo; I N P Aryantha (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
Science teacher education, including biology, pays more attention to the development of teacher knowledge to improve classroom management and student learning. Research on PCK in biology education has been carried out. However, accurate evaluation and documentation of what PCK researchers have done in biology education and what future researchers can do to develop biology teachers’ PCK must be comprehensively informed. Therefore, through the literature review, this study aimed to investigate the role of the biology teachers’ PCK on the quality of learning. This study employed a qualitative approach with the literature review method. Activities in this study included identifying the literature criteria to be reviewed, carrying out the literature selection process, analyzing the contents of the literature, synthesizing, and extracting data from the literature. From this stage, 10 works of literature were obtained for review and synthesis. The results of the study conducted indicate that knowing biology content is important for biology teachers, but that is not enough to teach biology, PCK are needed to realize meaningful learning. Besides, it was found that research on vertical content knowledge in biology education is rarely conducted. This leads to opportunities for vertical content knowledge research in biology education to improve teachers’ PCK